Behavioral Assessment of Expert Talent Competencies: Analysis, Decision Making, and Written and Verbal Communication Skills - Kord, Homayoon; Thornton III, George (Personnel Assessment and Decisions, 2020)
Organizations face challenges of screening applicants for critical skills to serve in expert staff positions requiring interactions with line managers. Such positions require a special set of cognitive and interpersonal competencies. This study investigates the psychometric qualities of a new behavioral assessment method in use in an applied setting. Using data from a group of 219 finalists for positions in a large Iranian steel company, it examined the validity and fairness of the method in relation to other test and demographic information. Results showed evidence of convergent and discriminant validity and no discrimination against women or older candidates. The study contributes to a clearer understanding of expert competencies and a practical method for assessing and training such competencies. Next steps and future needs are identified.